Memahami Dinamika Kegiatan Ekonomi dan Pembangunan Desa di Negara Berkembang: Studi Kasus di Pulau Jawa, Indonesia - Adi Saputra, Putu Mahardika (Sodality: Jurnal Sosiologi Pedesaan, 2023)
Indonesia as a country with very diverse regional typologies needs to pay attention to the effect of typological differences on the relationship between village administration human resources, village economic activities, and village development. This study examines the relationship between village administration human resources and village economic activities with village development in five provinces located on the island of Java, namely Banten, Special Region of Yogyakarta, West Java, Central Java, and East Java. Using the 2019 Village Potential Data (PODES), a descriptive statistical analysis was carried out for around twenty-two thousand recorded villages. In general, this study shows that in terms of IDM status, East Java province has the highest success in village development as indicated by the highest number of independent villages and developed villages compared to other provinces. Several other core variables, such as village administration human resources, village economic activities, and village development have unique performances in each of the analyzed provinces.